Proteomics in Biomarker Discovery for Tuberculosis: Current Status and Future Perspectives - Guo, Jiubiao; Zhang, Ximeng; Chen, Xinchun; Cai, Yi (Frontiers in Microbiology, 2022)
Tuberculosis (TB) continues threatening worldwide public health regardless of country or age. Current diagnosis of TB still mainly uses traditional time-consuming and/or culture-based techniques. Efforts have been focused on discovering new biomarker for TB diagnosis with reducing the time and increasing the amount of diagnostic information available. Proteomics is the systematic study of diversity of proteins and is growing applied to discover novel protein biomarkers for different types of diseases. Mass spectrometry (MS) technology plays a revolutionary role in promoting proteomics, and benefit from the development of other technologies, such as matrix based approaches and immune based methods, the MS technique and derivative strategies continuing contribute to diseases related studies. And some promising proteomic biomarkers for efficient TB diagnosis have been identified, but challenges still exist. For example, discrepancy of biomarkers identified among different reports, and diagnosis accuracy of the clinical application of proteomic biomarkers. The present review summaries the current status and future perspectives of proteomics in the field of TB biomarkers discovery, aim to elicit more promising findings for rapid and accurate TB diagnosis.